Worship: bowing down in the service of God. Issue 3 (September 2022) - Levi, Avital Hazony
Abstract: Philosophers commonly assume that worship is a universal attitude. Two major approaches see worship as a sui generis attitude or as the specific attitude of respect. This article criticizes the universal assumption and defines worship as a ritual that shapes a person in acquiring the attitude considered appropriate in relating to a superior such as God. Religions differ in their rituals of worship because they disagree on what this appropriate attitude is. This claim is demonstrated by distinguishing the Hebrew Bible's form of worship as bowing down. Biblical worship is shown to be political, forming the worshipper into a loyal servant of God as king. This form of worship is argued to be fundamentally ethical because it teaches that the individual's relationship with God supervenes on human relationships.